The relationship between the circular economy and business performance: a systematic literature review - Nosková, Marta; Taušl Procházková, Petra; Zemanová, Veronika (Journal of Business Economics and Management, 2024)
The circular economy represents an effective way to address limited resources and mitigate the impact of human activity on the planet. To summarize the possible effect of circular economy implementation on business performance and its possible measurement, a systematic literature review on a final sample of 28 papers was conducted. The main findings reveal that the circular economy can help to improve business performance and that numerous indicators could be used to measure it, especially the balanced scorecard approach, which seems suitable for such classification (however, more research on this topic is needed). Additionally, it was revealed that the circular economy concept itself has no clear and generally used definition, which complicates the summarizing of the revealed indicators. To simplify future research, we proposed a research framework based on this systematic literature review and emphasized the research gaps.